Reduced cerebrovascular reactivity in young adults carrying the APOE ε4 allele. - Suri, S; Mackay, C; Kelly, M; Germuska, M; Tunbridge, E; Frisoni, G; Matthews, P; Ebmeier, K; Bulte, D; Filippini, N (Elsevier, 2015)
BACKGROUND: Functional magnetic resonance imaging (MRI) studies have shown that APOE ε2- and ε4-carriers have similar patterns of blood-oxygenation-level-dependent (BOLD) activation suggesting that we need to look beyond the BOLD signal to link APOE's effect on the brain to Alzheimer's disease (AD)-risk. METHODS: We evaluated APOE-related differences in BOLD activation in response to a memory task, cerebrovascular reactivity using a CO2-inhalation challenge (CO2-CVR), and the potential contribution of CO2-CVR to the BOLD signal. RESULTS: APOE ε4-carriers had the highest task-related hippocampal BOLD signal relative to non-carriers. The largest differences in CO2-CVR were between ε2- and ε4-carriers, with the latter having the lowest values. Genotype differences in CO2-CVR accounted for ∼70% of hippocampal BOLD differences between groups. CONCLUSION: Because CO2-CVR gauges vascular health, the differential effect of APOE in young adults may reflect a vascular contribution to the vulnerability of ε4-carriers to late-life pathology. Studies confirming our findings are warranted.